EBXML messaging services for business to government (B2G) / Nor Khatijah Idrus - Idrus, Nor Khatijah (2010)
With today's increasing demand for businesses to communicate with each other, business-to-business (B2B) integration holds the key to successful e-commerce collaboration. However, the technology that have been use to integrate businesss application were proven unsuccessful when extended to the network infrastructure especially for fees. EbXML is a specification that enables enterprises of any size and in any geographical location to conduct business over the Internet without any fees payment for network infrastructure. It is defined as a set of layered extensions to the base Simple Object Access Protocol (SOAP). Business trading partner usually doing import/export transaction but because of the payment fee some enterprises such as Small Medium Enterprises (SME), this fee is burdening them. Ebxml Messaging Services for Business to Government (B2G) can improve inter-business work processes and provide highly reliable functions because there no charge for network infrastructure anymore and this system can be access by anyone and anywhere. In this project, SOAP technique is use to send Kl form to custom department. It is a communication protocol that provides a way to communicate between applications running on different operating systems, with different technologies and programming languages.